2014
DOI: 10.1038/srep04039
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Conductivity and Viscosity of Nanodiamond-Nickel Nanocomposite Nanofluids

Abstract: We report a new type of magnetic nanofluids, which is based on a hybrid composite of nanodiamond and nickel (ND-Ni) nanoparticles. We prepared the nanoparticles by an in-situ method involving the dispersion of caboxylated nanodiamond (c-ND) nanoparticles in ethylene glycol (EG) followed by mixing of nickel chloride and, at the reaction temperature of 140°C, the use of sodium borohydrate as the reducing agent to form the ND-Ni nanoparticles. We performed their detailed surface and magnetic characterization by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(64 citation statements)
references
References 53 publications
1
60
1
2
Order By: Relevance
“…Pastoriza-Gallego et al presented papers in which they describes the thermal conductivity of nanofluids increase with increasing temperature for Al 2 O 3 -EG [12], and ZnO-EG [36]. The increase in thermal conductivity with temperature in ethylene glycol based nanofluids was also reported by Yu et al [37], Timofeeva et al [38], and Sundar et al [39]. A similar correlation was presented by Abareshi et al [40] for Fe 3 O 4 -H 2 O, and by Colla et al [41] for Fe 2 O 3 -H 2 O nanofluids and in review article by Kleinstreuer and Feng [42].…”
Section: Introductionmentioning
confidence: 58%
“…Pastoriza-Gallego et al presented papers in which they describes the thermal conductivity of nanofluids increase with increasing temperature for Al 2 O 3 -EG [12], and ZnO-EG [36]. The increase in thermal conductivity with temperature in ethylene glycol based nanofluids was also reported by Yu et al [37], Timofeeva et al [38], and Sundar et al [39]. A similar correlation was presented by Abareshi et al [40] for Fe 3 O 4 -H 2 O, and by Colla et al [41] for Fe 2 O 3 -H 2 O nanofluids and in review article by Kleinstreuer and Feng [42].…”
Section: Introductionmentioning
confidence: 58%
“…Kumar et al [17] observed thermal conductivity enhancements of 36%, 42% and 48% for 0.5% volume concentrations of Zn, Cu, and Cu-Zn nanofluids, similarly, viscosity enhancements of 47%, 53%, and 61% respectively, compared to base fluid (vegetable oil). Sundar et al [18] synthesized nanodiamond-nickel nanocomposite using in-situ growth and chemical coprecipitate method and prepared nanofluids by dispersing ND-Ni in ethylene glycol and water mixture and estimated thermal conductivity and viscosity experimentally. Nine et al [19] prepared Al 2 O 3 -MWCNTs hybrid nanofluids in weight proportion of 97.5/2.5 to 90/10 and studied thermal properties in the weight concentrations of 1-6%.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, composite nanofluids require a stable dispersion of embedded composite nanoparticles and low hydrodynamic resistance for various applications such as energy, automobiles, welding equipment, laser diode arrays, microwave tubes, and so on 48 . In many cases, those applications are implemented using microstructural channels through which nanofluids flow in order to enhance the corresponding heat transfer efficiency 9, 10 .…”
Section: Introductionmentioning
confidence: 99%